Necesidad de establecer una institución jurídica en el código orgánico de la niñez y adolescencia, que determine la desestimación y archivo de la demanda de alimentos, cuando la parte actora no comparezca al examen de ADN. - Márquez Robles, Cornelio (2013)
The current Constitution of the Republic of the Ecuador settles down in its Art. 11 the equality of rights, duties and opportunities that we have all the Ecuadorians in diverse environments, such as the social, cultural, labor, in the civic participation and it could not be the exception in the procedural environment. Of the same one it is formed it guarantees in the Art. 76 numeral 7 the right to the defense that will be protected in all the stages of the procedure and in all the instances. The suitable equality in the defense in the step of legal foods doesn't exist, because the Title V Of the Right to Legal Foods of the Book Second of the Code of the Childhood and Adolescence, modified by the Reformatory Law s/n published in the Supplement of the R. O. Number 643 of July of the year 2009, in its Art. 10 establish a presumption in fact, which consists in that the negative one or nonappearance of the defendant to the practice of the exams of DNA (deoxyribonucleic acid), it makes presumes the filiation, and for likewise the alimentary obligation. But the case has not been legislated in that the demand part nonappearance to this medical tests, mainly for the reason that the demand part that is generally the minor’s mother, refuse to appear to the exams of DNA, it is that the presumed one alimentary is not the defendant's son, and for likewise the demand is simulated or fictitious, propose with the only purpose of obtaining an economic entrance of the defendant without legal reason exists for it, because the foundation of the legal food obligation is the bond filial parent. It arises the necessity to establish an juridical institution in the Code of the Childhood and Adolescence that it also protects the rights of the defendant part, then and it resides in that if the filiation presumption exists for the nonappearance from the defendant to the tests of DNA, a normative one that regulates the nonappearance of the demand part, should also settle down because it denotes deceit and simulation in the demand. An effective form of to reduce and to prevent that they think about feigned demands it is the underrating figure and file of the demand of legal foods when there is not appearance from the demand part to the test of DNA, with that which would be guaranteed the juridical security and equality of rights of both procedural parts.